Hambatan Aparat Penegak Hukum dalam Proses Penentuan Status Tersangka pada Tindak Pidana Penyalahgunaan Narkotika - Febriyana Pita Mantong; Syachdin; Muh Fikri (Al-Zayn : Jurnal Ilmu Sosial & Hukum, 2026)
This study aims to analyze the obstacles faced by law enforcement officers in the process of determining suspects in narcotics abuse cases and to examine the efforts that can be undertaken to overcome such challenges. The determination of a suspect constitutes a crucial stage in the criminal justice process, which must be carried out based on sufficient evidence in accordance with statutory regulations to ensure legal certainty, justice, and the protection of human rights. This research employs a normative legal research method by examining primary, secondary, and tertiary legal materials. The approaches used include the statutory approach, conceptual approach, and case approach. Legal materials were collected through library research by reviewing legislation, legal doctrines, court decisions, and relevant literature concerning narcotics abuse offenses.The findings reveal that law enforcement officers encounter various obstacles in the process of determining suspects, including limited evidence, difficulties in obtaining relevant witness testimonies, differing interpretations of the elements of narcotics-related crimes, and the complexity of narcotics distribution networks involving multiple parties. Furthermore, the need to safeguard suspects’ rights and comply with adequate evidentiary standards presents additional challenges in the suspect determination process. In conclusion, the determination of suspects in narcotics abuse cases requires accuracy and prudence on the part of law enforcement officers to prevent violations of human rights and procedural errors. Strengthening inter-agency coordination, enhancing the capacity of law enforcement personnel, and improving evidentiary mechanisms are essential measures to support the effectiveness of narcotics law enforcement.